The Burkitt affair revisited. Colonial implications and identity politics in early South African prehistoric research - (:unkn) unknown (My University, 2003)
The alleged professional misconduct of Cambridge prehistorian Miles Burkitt, over his guided archaeological trip to South Africa in 1927 and the single-authored publication that resulted, has been taken to epitomize colonial relations of expropriation. However, unexploited archival and printed resources show that the affair has far more interesting implications, and that in South Africa of the 1920s and 1930s prehistoric archaeology became something of a 'national discipline', bearing both on national prestige abroad and on national unity at home, in the stormy relations between the English-and Afrikaans-speaking communities.
Keywords: African Research